TINJAUAN YURIDIS TERHADAP PEMBANGUNAN RUMAH SUSUN YANG DIBANGUN DENGAN PEMANFAATAN BARANG MILIK NEGARA BERUPA TANAH BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN - FANDY JAPTO (PREMISE LAW JURNAL, 2014)
ABSTRACT   Low-cost apartments are built as the effort of the government to meet the need of society for proper housings in a healthy environment and as an alternative to solve the problem of land procurement, Article 18 of Law No.20/2011 on Apartment regulates the opportunity to build apartments on the state land. The state assets in the construction of apartments building can be done under leasing contract and joint-cooperation in utilizing State Land for the period of 60 years, only general and special apartments that can be built on the state-owned land, the government is responsible to provide guidance and incentives to the developers for the materialization of the construction and to provide guidance in the construction of apartment buildings. Thus, the government is suggested to make the regulation on the extension of lease of the State-owned land allocated for the construction of apartment buildings Keywords : Apartment, State Assets, State Land